Brucella abortus Strain RB51 Vaccine: Immune Response after Calfhood Vaccination and Field Investigation in Italian Cattle Population - Manuela Tittarelli; Barbara Bonfini; Fabrizio De Massis; Armando Giovannini; Mauro Di Ventura; Donatella Nannini; Vincenzo Caporale (Clinical and Developmental Immunology)
Immune response to Brucella abortus strain RB51 vaccine was measured in cattle vaccinated at calfhood. After an increase at day 6 post-vaccination (pv), the antibody level recorded in the 10 vaccinated animals remained constant for two months, and then progressively decreased. All vaccinated animals remained negative from day 162 pv to the end of the study (day 300 pv). Only at days 13 and 14 pv the RB51-CFT showed 100% sensitivity (credibility interval (CI) 76.2%–100%). The results indicate that the possibility to use RB51-CFT for the identification of cattle vaccinated at calfhood with RB51 is limited in time. A field investigation was carried out on 26,975 sera collected on regional basis from the Italian cattle population. The study outcomes indicate that in case of RB51-CFT positive results observed in officially Brucellosis-free (OBF) areas and, in any case, when an illegal use of RB51 vaccine is suspected, the use of the RB51-CFT alone is not sufficient to identify all the vaccinated animals. The design of a more sophisticated diagnostic protocol including an epidemiological investigation, the use of RB51-CFT, and the use of the skin test with RB51 as antigen is deemed more appropriate for the identification of RB51 vaccinated animals.